PERAN PEMERINTAH DAERAH DALAM PELESTARIAN SITUS SEJARAH DALAM RANGKA MENGOPTIMALKAN PENDAPATAN ASLI DAERAH : (Studi Kasus Di Taman Renungan Bung Karno Kabupaten Ende Nusa Tenggara Timur) - Umbu TW Pariangu; Agatha Christana Mitan Lewar; Petrus Kase (Halu Oleo University, 2024)
The aim of this research is to determine the role of local government in preserving historical sites in order to optimize local revenue and what factors hinder the preservation of Taman Renungan Bung Karno as a historical site in Ende Regency. This type of research is descriptive with a qualitative approach. The results of the research show that the role of local government in preserving historical sites at Taman Renungan Bung Karno in the aspects of motivator, facilitator and dynamist has not been carried out effectively. The government must be more active in carrying out innovations in promoting tourism and disseminating information regarding the Bung Karno Reflection Park through outreach activities and seminars. The government also needs to provide supporting infrastructure such as bathrooms/toilets which are vital tourist needs, repair damaged park facilities, including tightening supervision in the park.